48.4k views
4 votes
-3z - (3z - 2) = 4(z + 3)
Can someone please tell me what to do step by step Pleaseee

2 Answers

11 votes
yes that's correct^
User Aeefire
by
4.9k points
6 votes

Answer:

z = -1

Step-by-step explanation:

-3z - (3z - 2) = 4(z + 3)

Expand -3z - (3z - 2): -6z + 2

Expand 4(z + 3): 4z + 12

-6z + 2 = 4z + 12

Subtract 2 from both sides

-6z + 2 - 2 = 4z + 12 - 2

Simplify

-6z = 4z + 10

Subtract 4z from both sides

-6z - 4z = 4z + 10 - 4z

Simplify

-10z = 10

Divide both sides by -10

-10z / -10 = 10 / -10

Simplify

z = -1

- zyxx

User Zubda
by
4.2k points